PENDAMPINGAN PEMBUATAN NOMOR INDUK BERUSAHA(NIB) PADA UMKM DI DESA MUSIR KIDUL KECAMATAN REJOSO KABUPATEN NGANJUK - Finda Rohmatin Nakrowiyah; Niniek Imaningsih; Cholid Fadil (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Semen Hamlet, which is located in Musir Kidul Village, is now known as Dusun Tape because the majority of their MSMEs are tape entrepreneurs. However, in every business trip, it is necessary to have business legality to get legal protection from the government. It is not surprising that MSME actors in Musir Kidul Village have minimal business legality due to the lack of knowledge regarding this matter. One of the goals of this community service activity is to solve problems with MSMEs, especially regarding business legality by making a Business Identification Number (NIB). The implementation method used is the door to door method. There are three stages in this activity, namely the MSME survey, assistance in making NIB, and submission of NIB certificates. The result of this activity is that business actors can know the importance of business legality in their MSMEs and business registration into the OSS institution. Therefore, later MSME business actors who have registered NIB will receive business protection, ease of access to business capital, assistance to develop MSMEs, and empowerment from the government.